Biological Characterization and Preliminary Crystallization: A Step Towards the Use of Novel Allium sativum Protease Inhibitor as a Potential Therapeutic Drug - Shamsi, Tooba N.; Afreen, Sumbul; Parveen, Romana; Kumar, Manish; Fatma, Tasneem; Fatima, Sadaf (Current Enzyme Inhibition, 2021)
Background: Garlic, being a well-known medicinal plant, is the most commonly used culinary spice worldwide. Investigation of protease inhibitor isolated from garlic leads to a promising contender in pharmacognostic and pharmacological studies. Objective/Introduction: Protease Inhibitor (PI) from 'garlic' (Allium sativum) was analyzed for its biological role as an antioxidant, antimicrobial, and anti-inflammatory agent. Methods: Antioxidant activity was evaluated using ferric ion reducing antioxidant power (FRAP) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assays. The anti-inflammatory activity was assessed using trypsin inhibitory assay and heat-induced albumin denaturation method. The antimicrobial activity was examined in broth against E. coli and B. Subtilis. The crystallization was setup using the hanging drop method. Results: ASPI showed DPPH radical scavenging with IC50 values 561±0.337 μg/ml. Also, ASPI showed the highest value of 0.699±0.009 mM at 1000 μg/ml and the lowest i.e. 0.181±0.006 mM at 100 μg/ml in FRAP assay. Ascorbic acid was taken as standard in both cases. ASPI showed IC50 values of 651±0.532 μg/ml and 657±1.802 μg/ml, respectively. The antibacterial role of ASPI was testified, and results showed maximum inhibition against E. coli (ATCC 25922) i.e., 87.8 ±0.602% but no inhibition against B. subtilis (MTCC 736). Cuboidal shaped crystals of the ASPI were obtained in 4-6 weeks using 0.2M calcium chloride dihydrate, 0.1M sodium acetate trihydrate, 20 % isopropanol. Conclusion: ASPI has tremendous potential in the development of suitable drugs in pharmaceutical industries against diseases due to the generation of reactive oxygen species and cancer. The cuboidal crystals were obtained, which is the first study in the context of crystallization of ASPI to date.
Keywords: Allium sativum